ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN KREDIT CEPAT DAN AMAN PT.PEGADAIAN (PERSERO) UPC CIRENDEU - Delfi Yandri; Dewi Rahmah Fatmalia (ITB Swadharma, 2020)
During the last five years, the number of loans disbursed to the Indonesian people has increased (in trillions), namely in 2009 was 11,855; in 2010 is 15,021; the year 2011 was 19,872; in 2012 was 22,854; and in 2013 was 21.505 (BPS, 2016). Likewise, the development of the number of requests for credit disbursed by PT Pegadaian Cirendeu has increased in the last five years. The increasing number of requests for credit by the public provides an opportunity for PT Pegadaian as an alternative to channeling credit to the community, especially for the middle to lower class people who do not get credit facilities from banks. KCA (Fast and Secure Credit) is a loan from PT Pegadaian with a pawn system whose repayment is made by paying the loan money and capital rent and given to all groups of customers